2005
DOI: 10.1038/sj.ijo.0803135
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of diet-induced obesity by a combination of tea-catechin intake and regular swimming

Abstract: Objective: Obesity is a metabolic disorder resulting from imbalance between metabolizable energy intake and energy expenditure. It is known to be a strong risk factor for lifestyle-related diseases. Here, we investigated the effects of long-term intake of tea catechins (Cat) in combination with regular exercise (Ex) on the development of obesity in C57BL/6 mice. Design: We compared body weight, adipose tissue mass, plasma parameters and b-oxidation activity in mice fed a low-fat diet (5% triglyceride (TG); LF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
(46 reference statements)
1
40
0
Order By: Relevance
“…On the other hand, it is not clear whether catechin intake alone improves endurance capacity. Based on the results of the present study and a previous study (28), the effect of catechins alone might be limited because catechin intake alone had no marked effect on muscle metabolism, including fatty acid ␤-oxidation activity and mRNA expression. Rather, catechins seem to exert their main effects by stimulating hepatic lipid catabolism (26,28,39), which leads to reduced liver and abdominal fat weight and a lower plasma insulin level ( Table 2, 3).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…On the other hand, it is not clear whether catechin intake alone improves endurance capacity. Based on the results of the present study and a previous study (28), the effect of catechins alone might be limited because catechin intake alone had no marked effect on muscle metabolism, including fatty acid ␤-oxidation activity and mRNA expression. Rather, catechins seem to exert their main effects by stimulating hepatic lipid catabolism (26,28,39), which leads to reduced liver and abdominal fat weight and a lower plasma insulin level ( Table 2, 3).…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, tea catechins are proposed to be neuroprotective agents against progressive neurodegenerative disorders such as Parkinson's and Alzheimer's diseases (45). Thus, there is a growing interest in the application of tea catechins for disease prevention and treatment (49).We have been investigating the nutritional functions of tea catechins and demonstrated that long-term intake of tea catechins is beneficial for reducing diet-induced obesity in humans (30) and mice (26,28,39). More recently, we demonstrated that habitual intake of catechin-rich green tea extract (GTE) improves both swimming and running endurance capacity in normally-aging BALB/c mice (27,29).…”
mentioning
confidence: 99%
“…1,2). EGCG has been shown to be involved in regulation of a variety of metabolic processes and has been used as an anti-obesity reagent in animal models and in humans (3)(4)(5)(6). Although its effectiveness in the treatment of human diabetes has not been established, EGCG has been shown in rodents to be effective in preventing the development of Type I diabetes and treatment of Type II diabetes (7,8).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…22,23) Therefore, physical and pharmacological approaches that lead to sympathetic activation have been recommended for the management of obesity. 24) High doses of tea catechins are reported to inhibit catechol-o-methyltransferase (the enzyme that degrades catecholamines) in vitro 25) and increase VO 2 in HF diet-fed C57BL/6J mice, 26) but it remains unclear as to whether a KTE component is involved in the catechol pathway. In our previous study, KTE upregulated the expression levels of the genes associated with catecholamine metabolism, thus increasing the expression of catechol-o-methyltransferase and monoamine oxidase A (enzymes that degrade catecholamines) in C57BL/6J mice.…”
Section: Effect Of Kted On Vomentioning
confidence: 99%